The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1093/mnras/stz403
|View full text |Cite|
|
Sign up to set email alerts
|

Magnetic topologies of young suns: the weak-line T Tauri stars TWA 6 and TWA 8A

Abstract: We present a spectropolarimetric study of two weak-line T Tauri stars (wTTSs), TWA 6 and TWA 8A, as part of the MaTYSSE (Magnetic Topologies of Young Stars and the Survival of close-in giant Exoplanets) program. Both stars display significant Zeeman signatures that we have modelled using Zeeman Doppler Imaging (ZDI). The magnetic field of TWA 6 is split equally between poloidal and toroidal components, with the largest fraction of energy in higher-order modes, with a total unsigned flux of 840 G, and a poloida… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 84 publications
(138 reference statements)
3
24
0
Order By: Relevance
“…Coronal TTS X-ray emission indicates the presence of a strong surface magnetic field (Stassun et al 2006(Stassun et al , 2007. The typical mean-field strengths measured at the surface of classical (fully convective) TTS are 1-3 kG, and decrease to a few 100 G for weak-line (mainly radiative) TTS (Hill et al 2019;Villebrun et al 2019;Donati et al 2019;Sokal et al 2020). The dynamos producing these magnetic fields are driven by convective interior structure, typical of low-mass TTS evolving along Hayashi tracks.…”
Section: Introductionmentioning
confidence: 99%
“…Coronal TTS X-ray emission indicates the presence of a strong surface magnetic field (Stassun et al 2006(Stassun et al , 2007. The typical mean-field strengths measured at the surface of classical (fully convective) TTS are 1-3 kG, and decrease to a few 100 G for weak-line (mainly radiative) TTS (Hill et al 2019;Villebrun et al 2019;Donati et al 2019;Sokal et al 2020). The dynamos producing these magnetic fields are driven by convective interior structure, typical of low-mass TTS evolving along Hayashi tracks.…”
Section: Introductionmentioning
confidence: 99%
“…Bessolaz et al (2008) have studied the conditions for a steady accretion flow from a circumstellar disk in the presence of a dipolar stellar magnetic field. There are few measures of photospheric magnetic fields for low-mass (M * ≤ 0.5 M ) YSOs with typical values of B * ≈ 1 kG (e.g., Hill et al 2019;Lavail et al 2019), but fields of about 100 G and lower have also been observed (e.g., Donati et al 2010;Morin et al 2011). Based on Eq.…”
Section: Discussionmentioning
confidence: 99%
“…However, see Koen (2016) for a discussion of the possibility of abovephotospheric spot temperatures in WTTS. Furthermore, the surface brightness reconstructions made with Zeeman Doppler imaging for WTTSs by Donati et al (2014Donati et al ( , 2015Donati et al ( , 2017 and Hill et al (2017Hill et al ( , 2019 indicate the presence of cool spots and warm plages at the stellar surface of young stars with convective envelopes. Thus, the warm spots found for V1598 Cyg do not provide conclusive evidence for the binary nature of the source.…”
Section: Spot Properties On V1598 Cygmentioning
confidence: 92%